Strontium and Oxygen Isotope Analyses Reveal Late Cretaceous Shark Teeth in Iron Age Strata in the Southern Levant - Tütken, Thomas; Weber, Michael; Zohar, Irit; Helmy, Hassan; Bourgon, Nicolas; Lernau, Omri; Jochum, Klaus Peter; Sisma-Ventura, Guy (Frontiers in Ecology and Evolution, 2020)
Skeletal remains in archaeological strata are often assumed to be of similar ages. Here we show that combined Sr and O isotope analyses can serve as a powerful tool for assessing fish provenance and even for identifying fossil fish teeth in archaeological contexts. For this purpose, we established a reference Sr and O isotope dataset of extant fish teeth from major water bodies in the Southern Levant. Fossil shark teeth were identified within Iron Age cultural layers dating to 8-9th century BCE in the City of David, Jerusalem, although the reason for their presence remains unclear. Their enameloid 87Sr/86Sr and δ18OPO4 values (0.7075 ± 0.0001 (1 SD, n=7) and 19.6 ± 0.9 ‰ (1 SD, n=6), respectively), are both much lower than values typical for modern marine sharks from the Mediterranean Sea (0.7092 and 22.5‒24.6 ‰ (n=2), respectively). The sharks’ 87Sr/86Sr are also lower than those of rain- and groundwater as well as the main soil types in central Israel (≥0.7079). This indicates that these fossil sharks incorporated Sr (87Sr/86Sr »0.7075) from a marine habitat with values typical for Late Cretaceous seawater. This scenario is in line with the low shark enameloid δ18OPO4 values reflecting tooth formation in the warm tropical seawater of the Tethys Ocean. Age estimates using 87Sr/86Sr stratigraphy place these fossil shark teeth at around 80-Million-years-old. This was further supported by their taxonomy and the high dentine apatite crystallinity, low organic carbon, high U and Nd contents, characteristics that are typical for fossil specimens, and different from those of archaeological Gilthead seabream (Sparus aurata) teeth from the same cultural layers and another Chalcolithic site (Gilat). Chalcolithic and Iron Age seabream enameloid has seawater-like 87Sr/86Sr of 0.7091 ± 0.0001 (1 SD, n=6), as expected for modern marine fish. Fossil shark and archaeological Gilthead seabream teeth both preserve original, distinct enameloid 87Sr/86Sr and δ18OPO4 signatures reflecting their different aquatic habitats. Fifty percent of the analysed Gilthead seabream teeth derive from hypersaline seawater, indicating that these seabreams were exported from the hypersaline Bardawil Lagoon in Sinai (Egypt) to the Southern Levant since the Iron Age period and possibly even earlier.